Forecasting Nifty and Sensex Series using Theil’s U Statistic - Maheta, Dr.Dhaval (International Journal of Advanced Science and Technology, 2019)
There are lot of uncertainties involved in stock market prices. These uncertainties may be due to external or internal environments. The presence of these uncertainties makes the stock market volatile. These uncertainties can be current state of economy, political turmoil, global factors, etc. So it is necessary to map the trend of stock market. To predict the trends researcher has used ARIMA Model. By using ARIMA model also known as Box Jenkins Methodology we try to make model which can predict these uncertainties well in advance. In this paper, series of Nifty and Sensex is predicted using Box-Jenkins (ARIMA) approach.